Force decay of intermaxillary orthodontic elastics: in vitro study - Kardach, Hubert; Olszewska, Aneta; Firlej, Ewa; Bogdanowicz, Agnieszka; Golusińska-Kardach, Ewelina; Szponar-Żurowska, Anna; Biedziak, Barbara (Journal of Medical Science, 2019)
Introduction. Orthodontic elastics are widely used in orthodontic treatment. It’s been proved that they have advantages such as low cost, ease of use, but also disadvantages, mainly force decay in time and increased entrapment of biofilm. Amount of the force is of extreme significance. This force can be altered by physical or chemical factors. Material and Methods. Latex elastics in 3 different diameters were selected for this study. Each elastic was stretched and placed on hooks that are at specified distances that equal 3 times the diameter of each elastic. The forces produced by stretching was measured using tension gauge and the measurement were taken at specific time intervals of 0h, 3h, 12h, 24h. The same process was repeated for elastics in dry and artificial environment. Results. Elastics in the dry environment showed progressive force decay cause by stretching over time. Just after 3 hours force decay between 6,07% and 8,75% was observed. The biggest loss of force between 13,61 — 16,13 % was measured after 24 hours. Compared to the dry environment, an even more significant force decay was observed in the artificial saliva. After first 3 hours force loss was between 4,99% — 9,22%. The biggest force decay was observed after 24 hours and it was 5 % higher compared to dry environment. Conclusions. 1) The artificial saliva environment and time of exposure to it, have a negative effect on the properties of elastomeric. 2) To maintain the effective orthodontic strength of elastics, they should be replaced every 12 hours.
Keywords: force decay; orthodontic elastics; artificial saliva; elastomeric